ADDITION OF ALUMINIUM CAN FIBERS AND REINFORCED CONCRETE - Souza, Leandro Moreno De; Assis, Cleber Decarli de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The use of staple fibers with reinforcing function in some cases is better than conventional equipment with rods and wires. As in the case of thin sheets which do not contain reinforcement in the form of rods, fibers serving as the main armor, and the rate exceeds 5% by volume. Another case is the control of cracking due to humidity and temperature variations, where the fibers act as secondary armor. Although the concrete will gain strength with the addition of fibers, it is important to note that this gain is not specific varying according to the approximation of the fibers relative to the direction of the main tensile stress, so its primary function is to contain or avoid the appearance of cracks that impair the concrete structure, and that its use provides increased toughness and energy absorption capacity, where the voltage drop is accompanied by large deformation. This work aims to present an analysis of the use of steel fibers obtained by recycling aluminum cans added to the concrete fibers. Checking the possible changes in the mechanical behavior of concrete.